2017
DOI: 10.1002/mp.12492
|View full text |Cite
|
Sign up to set email alerts
|

Fully automatic, multiorgan segmentation in normal whole body magnetic resonance imaging (MRI), using classification forests (CFs), convolutional neural networks (CNNs), and a multi‐atlas (MA) approach

Abstract: Purpose: As part of a program to implement automatic lesion detection methods for whole body magnetic resonance imaging (MRI) in oncology, we have developed, evaluated, and compared three algorithms for fully automatic, multiorgan segmentation in healthy volunteers. Methods: The first algorithm is based on classification forests (CFs), the second is based on 3D convolutional neural networks (CNNs) and the third algorithm is based on a multi-atlas (MA) approach. We examined data from 51 healthy volunteers, scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 23 publications
4
36
0
1
Order By: Relevance
“…With the emergence of deep learning, neural networks have regained ground in medical image analysis [3]. Deep neural networks of fully convolutional [31]- [33] and especially of the U-net variant [34], [35] have achieved very good results in multiorgan segmentation. The effectiveness of these methods depends on the availability of large annotated datasets and GPUbased computing to optimize empirically defined network architectures that can have millions of parameters [35].…”
Section: A Multiorgan Segmentation Methodsmentioning
confidence: 99%
“…With the emergence of deep learning, neural networks have regained ground in medical image analysis [3]. Deep neural networks of fully convolutional [31]- [33] and especially of the U-net variant [34], [35] have achieved very good results in multiorgan segmentation. The effectiveness of these methods depends on the availability of large annotated datasets and GPUbased computing to optimize empirically defined network architectures that can have millions of parameters [35].…”
Section: A Multiorgan Segmentation Methodsmentioning
confidence: 99%
“…Therefore, we need to induce spatial priors in order to guide the second stage network with a better ROI. A multi-atlas technique was chosen for producing spatial priors, because with multi-atlas segmentation, although the segmentation accuracy is lower than CNN-based accuracy, it mostly generates good organ localisation [7]. As shown in Fig.1, the bladder segmentation result of multi-atlas is focused in one specific location instead of having multiple predictions scattered in other areas (shown in FCN probability maps).…”
Section: Roi Selectionmentioning
confidence: 99%
“…Our approach is substantially different from this previously published work as it includes the use of a 3D CNN approach, a substantially larger dataset and provides a comparison to alternative methods. Previous studies by other investigators have shown that CNN‐based methods outperform conventional image analysis techniques for segmentation problems across a variety of organs, such as brain tumours, other brain structures, liver lesions, pulmonary nodules, and multiorgan segmentation applied to the normal whole body (MRI) . We, therefore, anticipate expansion of this paradigm across a variety of cardiovascular applications.…”
Section: Introductionmentioning
confidence: 95%